High nutritional value instant flakes produced from various cereal grains - W. K. Galal; R. S. Abd El-Salam; A. M. Marie (Пищевые системы, 2024)
The current study was carried out to prepare functional flakes from various cereals and to assess the nutritional value of breakfast cereal flakes and their sensory acceptability. Oat, soft wheat and durum wheat, barley (hull-less and hulled), triticale, millet and sorghum grains have been used. Physicochemical, functional, phytochemical properties and sensory evaluation were determined. The developed cereal flakes have high nutritional value and are high in dietary fiber. Concerning the overall acceptability of flakes, durum wheat, hull-less barley and triticale were more preferred than the other samples. Meanwhile, hulled barley and millet flakes showed the lowest scores compared with other flake samples due to the lowest score of their appearance and color. Triticale, durum wheat and hulled barley turned to be good alternatives for oat to prepare flakes of high-quality characteristics, as they have high protein (13.46, 11.92 and 11.67%, respectively) and ash contents along with low content of fat and low calories. In terms of nutritional quality, the results indicated that oat flakes were higher in Mg and P content, durum wheat flakes showed higher content of Mn, triticale had the highest content of K and Ca, and millet had the highest content of Zn and Fe. Triticale flakes showed significantly higher content of dietary fiber and water absorption index at room and hot temperatures when compared with other flakes. While comparing total phenolic content, the millet and barley flakes showed the highest values. Additionally, most flake samples had significantly higher values of antioxidant activity compared to oat flakes used as control samples.